2016
DOI: 10.1515/geo-2016-0035
|View full text |Cite
|
Sign up to set email alerts
|

Usability evaluation of centered time cartograms

Abstract: Abstract:A time cartogram visualizes travelling-times between locations. It replaces the geographic distance by time distance and distorts the underlying map accordingly. By distorting the map, time cartograms may give a more intuitive and clear picture of travelling-times. The distortion of the map, however, can make time cartograms harder to recognize and use. Although cartograms are becoming widespread in use, very little is known about their usability. This study focuses on the usability of centered time c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Cartograms constitute thematic map visualizations that are mainly used in order to represent phenomena distributed in space (e.g., population mapping). In recent years, this type of visualization has become popular, having several applications in different domains [35], and especially fields related to cartography [36,37] and spatial analysis [38], providing fruitful information related to socio-economic conditions (see, e.g., the work presented in [39]). The implementation of a cartogram is based on the proportional distortion of a feature distance or area according to the value of the data that have to be visualized [40].…”
Section: Contiguous Irregular Cartogramsmentioning
confidence: 99%
“…Cartograms constitute thematic map visualizations that are mainly used in order to represent phenomena distributed in space (e.g., population mapping). In recent years, this type of visualization has become popular, having several applications in different domains [35], and especially fields related to cartography [36,37] and spatial analysis [38], providing fruitful information related to socio-economic conditions (see, e.g., the work presented in [39]). The implementation of a cartogram is based on the proportional distortion of a feature distance or area according to the value of the data that have to be visualized [40].…”
Section: Contiguous Irregular Cartogramsmentioning
confidence: 99%
“…This concentric isochrons are also known as centered travel-time cartograms. Another category depicts the travel time between all the pairs of locations, which is called noncentered travel-time cartogram [17][18][19][20][21][22]. A cartogram is a novel method to represent the geographical distribution of statistical datasets, which uses certain mathematical principles to transform a map so that the areas or distances on the map are proportional to the attribute values [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…The authors found that thematic maps were rated as more suitable than cartograms to map quantitative data. Another example is the work by Ullah et al. (2016), which involved carrying out a laboratory test with the general public.…”
Section: Introductionmentioning
confidence: 99%